Efektivitas Gaya Kepemimpinan dan Lingkungan Kerja dalam Meningkatkan Produktivitas Karyawan - Eka Septi Hartina; Ruli Haris (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
This study examines the influence of leadership style and work environment on employee productivity at PT Universal Carpet & Rugs. Using a quantitative associative approach, this research involved all 76 employees as respondents through a cencus method. The findings reveal that effective leadership and a conducive work environment play crucial roles in enhancing employee productivity. Among the two factors, the work environment show a more dominant effect. This study provides a unique contribution by demonstrating how physical and non-physical aspects of the work environment strengthen the impact of leadership effectiveness on employee outcomes. The results reinforce the significance of human resource management strategies that integrate leadership devolopment and workplace improvement in the manufacturing sector.